Pengaruh Kemampuan Literasi Membaca Terhadap Capaian Hasil Belajar Bahasa Indonesia Siswa Kelas V SD N 1 Kabanjahe - Erna Wati; Vera Charoline Br Barus (Peneliti.net, 2026)
Indonesian language learning at the elementary school level serves as a crucial foundation for building national identity and students' communication competencies. This study aims to determine the relationship between reading literacy capabilities and the learning outcomes of fifth-grade students at SD N 1 Kabanjahe. The method used in this research is a quantitative correlational design with a total sampling technique involving 28 students. Data were collected using reading literacy tests and documentation of academic scores. Data analysis included descriptive statistics, normality tests, and simple linear regression using SPSS. The results show a positive and significant relationship between reading literacy and student learning outcomes, with a significance value of 0.002 < 0.05. The calculated t-value of 2.814 > t-table 2.056, and the R Square value of 0.264 indicates that reading literacy contributes 26.4% to Indonesian language learning outcomes. These findings emphasize that improving students' literacy through active and sustainable strategies is a key factor in maximizing academic achievement at the primary school level